Compositions, lithium-ion batteries, and lithium-air batteries

CN116264280BActive Publication Date: 2026-10-27TOYOTA JIDOSHA KK +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211596842.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-13
Filing Date
2022-12-12
Publication Date
2026-10-27
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

[0004]用于Li离子电池和Li-空气电池中阴极电极的常规粘合剂分别是PVDF和这些聚合物不具有任何锂传导率,因此增加电芯的总电阻

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116264280B_ABST
    Figure CN116264280B_ABST
Patent Text Reader

Abstract

The present invention relates to a composition, a lithium-ion battery, and a lithium-air battery. The composition comprises (A) a mixed oxide of lithium, nickel, manganese, and cobalt and (B) a fluorinated anion salt of a polycationic polymer. The fluorinated anion salt of the polycationic polymer contains a repeating unit represented by one of Formula (1) or Formula (2): wherein, in Formula (1), N + is a nitrogen atom constituting a quaternary ammonium cation, R 1 and R 2 are each independently a substituent containing a carbon atom bonded to the nitrogen atom, wherein, in Formula (2), R 3 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to compositions of particular interest as cathode materials for use in secondary batteries, especially lithium-ion batteries and lithium-air (lithium-O2) batteries. It also relates to secondary batteries with different types of electrolytes, including liquid electrolytes and gel polymer electrolytes. Background Technology

[0002] Lithium-ion batteries are widely used in a variety of technologies. On the positive electrode side of the battery, which acts as the cathode during discharge, cathode materials containing lithium nickel manganese cobalt oxide (NMC) as described in non-patent reference (4) are known. NMC batteries are useful in electric vehicles and energy storage systems (ESS).

[0003] Lithium-air batteries have attracted attention as rechargeable batteries for battery-electric and hybrid vehicles requiring high energy density. Lithium-air batteries use oxygen from the air as the cathode active material. In metal-air batteries, the oxygen cathode active material is not contained within the battery. Instead, this material is provided by the surrounding atmosphere. Naturally, such a system allows for very high specific energy (energy provided per unit weight of battery, typically given in this art as Wh / kg). Therefore, lithium-air batteries are capable of having much larger capacities compared to conventional lithium batteries that contain transition metal oxides (e.g., lithium cobalt oxide) as the cathode active material.

[0004] Conventional binders used for cathode electrodes in Li-ion batteries and Li-air batteries are PVDF and [other binders]. These polymers do not have any lithium conductivity, thus increasing the total resistance of the cell.

[0005] Non-patent reference (1) discloses the manufacture and material composition of a solid electrolyte for Li-ion batteries. It mentions the possibility of using a polyionic liquid, such as PDADMA-TFSI, at the interface between the cathode and the solid electrolyte, where PDADMA is poly(diallyldimethylammonium) and TFSI is bis(trifluoromethanesulfonyl)imide. Non-patent reference (2) discloses the use of PDADMA-TFSI in electrolyte formulations.

[0006] Non-patent reference (3) discloses the manufacture and material composition of an adhesive for Li-S batteries. Here, PDADMA-Cl is used to form a crosslinking adhesive with ammonium functional groups. Non-patent reference (4) discloses the use of PDADMA-TFSI as an adhesive for Na-air batteries. The authors compared the performance using PVDF and PTFE. The electrolyte can be prepared with 16.6 mol% NaTFSI in a [C4mpyr][TFSI] ionic liquid. Only one cycle of discharge / charge was studied; the cell was not cycled.

[0007] Non-patent references

[0008] (1) Pont, AL; Marcilla, R.; De Meatza, I.; Grande, H.; Mecerreyes, D. Pyrrolidinium-Based Polymeric Ionic Liquids as Mechanically and Electrochemically Stable Polymer Electrolytes. J. Power Sources 2009, 188(2), 558–563.

[0009] https: / / doi.org / 10.1016 / j.jpowsour.2008.11.115

[0010] (2) Tomé, LC; Isik, M.; Freire, CSR; Mecerreyes, D.; Marrucho, IM Novel Pyrrolidinium-Based Polymeric Ionic Liquids with Cyano Counter-Anions:HIGHPerformance Membrane Materials for Post-Combustion CO2Separation.J.Memb.Sci.2015,483,155–165

[0011] (3)Liao,J.;Ye,Z.Quaternary Ammonium Cationic Polymer as a SuperiorBifunctional Binder for Lithium–sulfur Batteries and Effects of CounterAnion.Electrochim.Acta 2018,259,626–636.

[0012] https: / / doi.org / 10.1016 / j.electacta.2017.10.194.

[0013] (4)The An Ha et al., Functional Binders Based on Polymeric IonicLiquids for Sodium Oxygen Batteries Using Ionic Liquid Electrolytes

[0014] https: / / doi.org / 10.1021 / acsaem.0c02352

[0015] (5)Wladislaw Waag,Stefan Kabitz,DUSEExperimental Investigation of the Lithium-Ion Battery Impedance Characteristic at Various Conditions andAging States and Its Influence on the Application.Appl.Energy

[0016] Patent References

[0017] (1)EP 3 439 072

[0018] (2)JP 2019 021538

[0019] (3)WO 2020 237364 Summary of the Invention

[0020] In the context of NMC cathode binders in Li-ion batteries, conventional binders such as PVDF do not necessarily provide high performance in terms of capacity or resistance.

[0021] In the context of adhesives used for the air electrode (cathode) in Li-O2 batteries, Membranes do not necessarily provide optimal rate of use and / or capacity.

[0022] The present invention seeks to provide an adhesive that can achieve high performance when applied in the cathodes of Li-ion batteries and Li-O2 batteries.

[0023] The composition according to a first aspect of the invention comprises:

[0024] (A) A mixed oxide of lithium, nickel, manganese, and cobalt; and

[0025] (B) Fluorinated anionic salts of polycationic polymers containing repeating units represented by one of formulas (1) or (2):

[0026]

[0027] In equation (1), N + For the nitrogen atom that constitutes the quaternary ammonium cation, R 1 and R 2 Each of these is independently a substituent containing a carbon atom bonded to the nitrogen atom.

[0028]

[0029] In equation (2), R 3 It consists of hydrogen atoms or alkyl groups having 1 to 4 carbon atoms.

[0030] In the composition according to the first aspect of the invention, R in formula (1) 1 and R 2 Each can be an alkyl group.

[0031] In the composition according to the first aspect of the invention, R in formula (1) 1 and R 2 Both can be methyl groups.

[0032] In the composition according to the first aspect of the invention, R in formula (1) 1 It can be a methyl group and R in formula (1) 2 It can be a butyl group.

[0033] In the composition according to the first aspect of the invention, R in formula (2) 3 It can be an ethyl group.

[0034] In the composition according to the first aspect of the invention, the fluorinated anionic salt of the polycationic polymer may contain an imide anion of formula (3) as a fluorinated counterion of the polycationic polymer:

[0035] (F-(CF2) n -(SO2)-)2N - (3)

[0036] Where n = 0, 1 or 2.

[0037] In the composition according to the first aspect of the invention, the fluorinated anionic salt of the polycationic polymer may contain an imide anion having one of the following structures as a fluorinated counterion of the polycationic polymer:

[0038]

[0039] In the composition according to the first aspect of the invention, the fluorinated anion salt of the polycationic polymer may contain a perfluoroalkyl sulfonate of formula (4) as a fluorinated counterion of the polycationic polymer:

[0040] F-(CF2) n -(SO3) - (4)

[0041] Where n is an integer from 1 to 6.

[0042] In the composition according to the first aspect of the invention, n may be 4 in the perfluoroalkyl sulfonate group of formula (4).

[0043] In the composition according to the first aspect of the invention, the mixed oxide of lithium, nickel, manganese and cobalt may have the general formula (5):

[0044] LiNi x Mn y Co z O 2±α (5)

[0045] Where x+y+z=1.0 and α is at most 0.05.

[0046] In the composition according to the first aspect of the invention, x may be 0.5, y may be 0.3 and z may be 0.2.

[0047] In the composition according to the first aspect of the invention, x may be 0.33, y may be 0.33 and z may be 0.33, or x may be 0.6, y may be 0.2 and z may be 0.2, or x may be 0.8, y may be 0.1 and z may be 0.1.

[0048] The lithium-ion battery according to a second aspect of the present invention may comprise:

[0049] - A cathode comprising a positive electrode active material, said positive electrode active material comprising a composition containing the above-mentioned components (A) and (B);

[0050] - Including the anode, which is a negative electrode active material; and

[0051] - An electrolyte disposed between the anode and the cathode.

[0052] The lithium-air battery according to a third aspect of the present invention comprises:

[0053] - An anode containing a negative electrode active material;

[0054] - The cathode uses oxygen as the positive electrode active material; and

[0055] - An electrolyte disposed between the anode and the cathode.

[0056] The cathode comprises a fluorinated anionic salt of a polycationic polymer containing repeating units represented by either formula (1) or formula (2):

[0057]

[0058] In equation (1), N + For the nitrogen atom that constitutes the quaternary ammonium cation, R 1 and R 2 Each of these is independently a substituent containing a carbon atom bonded to the nitrogen atom.

[0059]

[0060] In equation (2), R 3 It consists of hydrogen atoms or alkyl groups having 1 to 4 carbon atoms.

[0061] In a lithium-air battery according to a third aspect of the invention, the fluorinated anion salt of the polycationic polymer may contain an imide anion of formula (3) as a fluorinated counterion of the polycationic polymer:

[0062] (F-(CF2) n -(SO2)-)2N - (3)

[0063] Where n = 0, 1, or 2,

[0064] Alternatively, a perfluoroalkyl sulfonate group of formula (4) may be included as the fluorinated counterion of the polycationic polymer:

[0065] F-(CF2) n -(SO3) - (4)

[0066] Where n is an integer from 1 to 6.

[0067] In the lithium-air battery according to the third aspect of the invention, the cathode may contain carbon.

[0068] In the lithium-air battery according to the third aspect of the invention, the carbon may be selected from one or more of the following types: carbon black, graphite, activated carbon, carbon nanofibers, carbon foam, molecular carbon, tubular carbon, and N-doped carbon.

[0069] In the lithium-air battery according to the third aspect of the invention, the carbon may exhibit one, two, or three of the following characteristics:

[0070] -in 20 and 2000m 2 Specific surface area between / g; and / or

[0071] -5nm or larger aperture diameter; and / or

[0072] The average primary particle diameter ranges from -8 to 350 nm.

[0073] In the lithium-air battery according to the third aspect of the invention, the liquid portion of the electrolyte may contain one or more aprotic organic solvents selected from the following: cyclic carbonates, chain carbonates, cyclic esters, cyclic ethers, chain ethers, and nitriles.

[0074] In the lithium-air battery according to the third aspect of the invention, the electrolyte may contain a lithium salt selected from the group consisting of LiClO4, LiTFSI and LiPF6. Attached Figure Description

[0075] Figure 1 The FT-IR spectra of the obtained polymer are shown in comparison with PDADMA-Cl.

[0076] Figure 2 Showing PDADMA-BETI 1 1H NMR spectrum (BETI is bis(perfluoroethyl sulfonyl)imide).

[0077] Figure 3 Showing PDADMA-BETI 13 C10 NMR spectrum.

[0078] Figure 4 Showing PDADMA-BETI 19 F NMR spectrum.

[0079] Figure 5 This illustrates a constant current discharge-charge test.

[0080] Figure 6 The resistance measurement is shown.

[0081] Figure 7A This shows a long constant current discharge-charge cycle test performed at 3C at 25°C.

[0082] Figure 7B This shows a long constant current discharge-charge cycle test performed at 3C at 50°C.

[0083] Figure 8A This shows a constant current discharge-charge test on a Li-O2 cell (Li-O2 battery).

[0084] Figure 8Bshows the galvanostatic discharge-charge test of a Li-O2 cell (Li-O2 battery).

[0085] Figure 9A shows the limited-capacity galvanostatic discharge-charge of a comparative example Li-O2 cell (Li-O2 battery).

[0086] Figure 9B shows the limited-capacity galvanostatic discharge-charge of Example 4.

[0087] Figure 10 shows the rate test of a Li-O2 cell (Li-O2 battery). DETAILED DESCRIPTION

[0088] <Li-ion battery>

[0089] The present invention relates to a binder composition for NMC cathodes in Li-ion batteries.

[0090] The abbreviation "NMC" is commonly used in the technical field to refer to a mixed oxide of lithium, nickel, manganese and cobalt used as a cathode in lithium-ion batteries. In the present invention, the inventors have found that favorable battery performance can be achieved in a lithium-ion battery having a positive electrode active material, which comprises a mixture of an NMC-type mixed oxide (on one hand) and a poly(ionic liquid) (on the other hand), and the poly(ionic liquid) contains certain types of polycations and fluorinated anions, such as particularly FSI, TFSI, BETI and –C4F9-SO3.

[0091] The lithium-ion battery of the present invention comprises: a cathode containing the positive electrode active material of the present invention; an anode; and an electrolyte. A separator may also be disposed between the anode and the cathode.

[0092] A current collector may be used, which is not particularly limited, and known materials and designs may be used. The current collector may be, for example, a two-dimensional conductive support such as a solid sheet or a perforated sheet, which is based on carbon or a metal such as nickel, steel, stainless steel or aluminum.

[0093] (Cathode for Li-ion battery)

[0094] The positive electrode active material of the present invention, present in the cathode, contains: (A) a mixed oxide of lithium, nickel, manganese and cobalt; and (B) a fluorinated anion salt of a polycationic polymer containing a repeating unit represented by the aforementioned formula (1) or (2).

[0095] Many (B) materials (fluorinated anionic salts of polycationic polymers containing repeating units represented by formula (1) or (2) above) are commercially available or can be obtained by well-established synthesis, as detailed, for example, in the review by Asshaplov et al.: “Recent Advances in Innovative Polymer Electroytes based on Poly(ionic liquid)s”, Electrochimica Acta, 2015. http: / / dx.doi.org / 10.1016 / j.electacta.2015.03.038 ).

[0096] In the composition used in the cathode of the Li-ion battery of the present invention, R in formula (1) 1 and R 2 Each can be an alkyl group. The alkyl group can be a methyl group, an ethyl group, a propyl group, or a butyl group. In formula (1), R... 1 and R 2 All can be methyl groups, or R in formula (1) 1 It can be a methyl group and R 2 It can be a butyl group.

[0097] In the composition used in the cathode of the Li-ion battery of the present invention, the fluorinated anion salt of the polycationic polymer may contain repeating units represented by formula (2), wherein R in formula (2) 3 It can be an ethyl group.

[0098] The weight-average molecular weight Mw of polycationic polymers containing repeating units represented by formula (1) or (2) can be between 50,000 and 1,000,000. For polycationic polymers containing repeating units represented by formula (1), the Mw range can be greater than 350,000, or between 400,000 and 500,000.

[0099] The fluorinated anionic salt of the polycationic polymer may contain an imide anion of formula (3) as a fluorinated counterion of the polycationic polymer:

[0100] (F-(CF2) n -(SO2)-)2N - (3)

[0101] Where n = 0, 1 or 2.

[0102] In addition to symmetrical imide anions with fluoroalkyl chains of equal length on both sides of the nitrogen atom, asymmetrical imide anions are also applicable, such as the anions with n=0, 1 and n=1, 4 shown below:

[0103]

[0104] The fluorinated anionic salt of the polycationic polymer may contain a perfluoroalkyl sulfonate group of formula (4) as a fluorinated counterion of the polycationic polymer:

[0105] F-(CF2) n -(SO3) - (4)

[0106] Where n is an integer from 1 to 6. In the perfluoroalkyl sulfonate group of formula (4), n can be 4.

[0107] In this invention, material (B) can be called PDADMA (corresponding to formula (1), where R 1 and R 2 All of them contain methyl groups. PDADMA is a polycationic substance of poly(diallyl dimethylammonium) and a salt of one of the following perfluorinated anions:

[0108] FSI = Bis(fluorosulfonyl)imide;

[0109] TFSI = bis((trifluoromethyl)sulfonyl)imide;

[0110] BETI = bis((perfluoroethyl)sulfonyl)imide; and

[0111] CFSO = Nano-fluorine-1-butanesulfonate.

[0112] When combining the fluorinated anion and the polycationic polymer in component (B) of the present invention, the polycationic polymer is typically initially prepared using a halogen counterion anion such as a chloride ion and is commercially available. Similarly, the fluorinated anion is typically initially prepared as a salt of an alkali metal cation (e.g., a lithium, sodium, or potassium salt) and is commercially available.

[0113] When the total weight of the positive electrode material is considered to be 100 wt%, the amount of fluorinated anionic salt of (B) polycationic polymer can be 2 wt% to 10 wt%.

[0114] Regarding (A) a mixed oxide of lithium, nickel, manganese and cobalt, it may have the general formula (5):

[0115] LiNi x Mn y Co z O 2±α (5)

[0116] Where x+y+z=1.0 and α is at most 0.05.

[0117] In the mixed oxides of this invention, x can be 0.5, y can be 0.3, and z can be 0.2. This is referred to in the prior art as "NMC523" and "NMC532". Other oxides as component (A) may include those commonly referred to in the prior art as "NMC 811" (x = 0.8, y = 0.1, and z = 0.1), "NMC 622" (x = 0.6, y = 0.2, and z = 0.2), and "NMC111" (x = 0.33, y = 0.33, and z = 0.33).

[0118] When the total weight of the positive electrode material can be considered as 100 wt%, the amount of (A) mixed oxide of lithium, nickel, manganese and cobalt can be 90 wt% to 95 wt%.

[0119] Carbon, such as acetylene black, can also be appropriately used as an additive to improve the electronic conductivity of the electrode. When the total weight of the positive electrode material is considered to be 100 wt%, this ratio can be similar to the ratio of the binder (B), i.e., 2 wt% to 10 wt%.

[0120] (anode)

[0121] There are no particular restrictions on the structure of the negative electrode (or anode), and known anode active materials can be used, as long as the material can serve as the negative electrode active material for a lithium-ion battery. For example, the anode active material may include carbon-based negative electrode active materials such as graphite and coke, alloy-based negative electrode active materials such as Si and / or Sn, lithium metal, lithium titanate oxide (LTO), or blends thereof.

[0122] (electrolyte)

[0123] The electrolyte may be a known non-aqueous electrolyte containing a lithium salt dissolved in a solvent.

[0124] There are no particular restrictions on the lithium salt; known lithium salts used in non-aqueous lithium-ion batteries can be used. The electrolyte salt may contain one or more of lithium bis(fluorosulfonyl)imide (“LiFSI”), lithium bis(trifluoromethanesulfonyl)imide (“LiTFSI”), LiBF4, lithium bis(oxalatoborate) (“LiBOB”), LiClO4, LiAsF6, LiPF6, LiCF3SO3, lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium (“LiTDI”), and LiPO2F2. The salt concentration may be in the range of 0.1 to 5.0 M. The lithium salt concentration in the electrolyte may be greater than 1.0 M, greater than 1.5 M, and greater than 2.0 M. The salt concentration may also be less than 4.0 M, less than 3.2 M, and less than 2.0 M.

[0125] In addition, the adhesive can be used with ionic liquid-based electrolytes or gel polymer electrolytes.

[0126] The solvent is not particularly limited, and known solvents used in non-aqueous lithium-ion batteries can be used. The solvent may be a single solvent or a mixture of solvents. The solvent may be selected from common organic solvents, especially saturated cyclic carbonates, unsaturated cyclic carbonates, acyclic (or linear) carbonates, alkyl esters (such as formates, acetates, propionates or butyrates), ethers, lactones such as γ-butyrolactone, tetrahydrothiophene dioxide, nitrile solvents and mixtures thereof. Among such saturated cyclic carbonates, specific examples that may be mentioned include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and mixtures thereof. Among unsaturated cyclic carbonates, specific examples that may be mentioned include vinylene carbonate (VC), derivatives thereof and mixtures thereof. Among acyclic carbonates, specific examples that may be mentioned include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC) and mixtures thereof. Among alkyl esters, specific examples that may be mentioned include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and mixtures thereof. Among ethers, examples that may be mentioned include dimethyl ether (DME) or diethyl ether (DEE), and mixtures thereof. Known fluorinated solvents can also be used, including for example fluorinated benzenes (such as hexafluorobenzene, pentafluorobenzene, 1,2,3,4-tetrafluorobenzene, etc.), fluorine-substituted linear carbonates and the like. In the present invention, gel polymer electrolytes are also applicable electrolyte materials.

[0127] (Separator)

[0128] The separator is not particularly limited, and known separators used in non-aqueous lithium-ion batteries can be used. The separator allows Li + to pass through and prevents electrical contact between the anode and the cathode. In one embodiment, the separator is a microporous membrane made of a polyolefin-based material, such as a microporous membrane made of polyethylene (PE), polypropylene (PP) or the like.

[0129] The separator material may be glass fiber, for example, a commercially available glass fiber ( Grade GF6, Schleicher & Schüll).

[0130] <Li-air battery>

[0131] (Anode)

[0132] In the lithium-air battery according to the third aspect of the present invention, the negative electrode (which may also be referred to as "anode" hereinafter) contains at least an anode active material (which may also be referred to as "negative electrode active material" hereinafter). As the anode active material, general anode active materials for lithium batteries can be used and the anode active material is not particularly limited. In general, the anode active material is capable of storing / releasing lithium ions (Li + ).

[0133] Specific anode active materials used in lithium-air batteries include, for example, lithium metal, lithium-protected anodes, lithium alloys (e.g., lithium-aluminum alloys, lithium-tin alloys, lithium-lead alloys, and lithium-silicon alloys), metal oxides (e.g., tin oxides, silicon oxides, lithium-titanium oxides, niobium oxides, and tungsten oxides), metal sulfides (e.g., tin sulfides and titanium sulfides), metal nitrides (e.g., lithium-cobalt nitrides, lithium-iron nitrides, and lithium-manganese nitrides), and carbonaceous materials (e.g., graphite).

[0134] Here, "lithium-protected anode" means, for example (but not limited to), "lithium-protected electrode" (LPE). Typically, Li is covered by a solid electrolyte (e.g., LISICON having the formula LiM2(PO4)3). An intermediate layer (e.g., composed of Cu3N / Li3N) is usually present between the LiSiCON and the Li metal. In the LPE system, the Li metal can be directly attached to one side of the LiSiCON material, or alternatively, a small amount of solvent containing a Li salt electrolyte can be added between the LiSiCON material and the Li metal to ensure Li ion conductivity. Such materials have been described, for example, in US7282295 and US 7491458.

[0135] When a foil or metal alloy is used as an anode active material, it can be used as the anode itself.

[0136] The anode needs to contain at least anodic active material; however, it may contain an adhesive for fixing the anodic active material, if required. The type and amount of adhesive are the same as those described below for air cathodes, so they will not be described here.

[0137] Generally, the anode current collector is connected to the anode and collects the current from the anode. There are no particular restrictions on the materials used for the anode current collector or its shape. Examples of materials used for the anode current collector include stainless steel, copper, and nickel. Examples of forms of the anode current collector include foil, plate, and mesh (grid) shapes.

[0138] (Cathode for Li-air batteries)

[0139] In the lithium-air battery of the present invention, oxygen is used as the positive electrode active material. The oxygen serving as the positive electrode active material can be contained in air or oxygen gas.

[0140] The positive electrode active material of the present invention present in the cathode comprises a fluorinated anionic salt of a polycationic polymer containing repeating units represented by formula (1) or (2) above, for the first aspect of the lithium ion of the present invention (B).

[0141] (B) The material may be a polycationic substance called PDADMA (which is poly(diallyl dimethylammonium)) and a salt of one of the following perfluorinated anions:

[0142] FSI = Bis(fluorosulfonyl)imide;

[0143] TFSI = bis((trifluoromethyl)sulfonyl)imide;

[0144] BETI = bis((perfluoroethyl)sulfonyl)imide; and

[0145] CFSO = Nano-fluorine-1-butanesulfonate.

[0146] Relative to the total weight of the positive electrode material, which is considered to be 100 wt% of the entire positive electrode consisting of a gas diffusion layer (GDL) and a slurry, the amount of the fluorinated anionic salt of the (B) polycationic polymer may be 2 wt% to 4 wt%, wherein the slurry may be carbon and binder in a ratio of 80 wt% carbon: 20 wt% binder.

[0147] In the lithium-air battery of the present invention, the positive electrode may contain carbon. Examples of carbon may include carbon black such as Ketjen black, acetylene black, channel black, furnace black, lamp black, and thermal black; graphite such as natural graphite such as flake graphite, artificial graphite, and expanded graphite; activated carbon from charcoal and coal; carbon foam; carbon fibers obtained by carbonizing synthetic fibers and petroleum pitch-based materials; carbon nanofibers; molecular carbon such as fullerenes; and tubular carbon such as carbon nanotubes. Modified carbon, such as N-doped carbon, may also be used.

[0148] In the lithium-air battery of the present invention, positive electrode materials based on materials other than carbon can also be used. For example, positive electrode materials based on metal foam, stable and conductive metal oxides, or steel can be used.

[0149] In this invention, when carbon is used, a porous material in powder form can be used, and the porous material can have a diameter of 20 to 2000 μm. 2 / g, 60 to 2000m 2 / g or 60 to 1500m 2High specific surface area per g. For example, carbon that has been treated by general methods to increase porosity or surface area, followed by further treatment to improve wettability, can be used. Examples of commercially available carbon products that can be used in this invention include the KS, SFG, Super P, and Super S series available from TIMCAL Ltd., activated carbon products available from Norit, Black Pearl and AB-Vulcan 72 available from Cabot, and KB-ECP and KB-ECP600JD available from KB International. Other examples of commercially available carbon include the WAC powder series available from XiamenAll Carbon Corporation, PW15-, J-, and S-type activated carbon available from Kureha, and Maxsorb MSP-15 available from Kansai Netsu Kagaku.

[0150] Generally, an air cathode current collector is connected to an air cathode and collects the current from the air cathode. There are no particular limitations on the materials or shapes used for the air cathode current collector. Examples of materials used for air cathode current collectors include stainless steel, aluminum, iron, nickel, titanium, and carbon. Examples of forms of air cathode current collectors include foil, plate, mesh (grid), and fiber. Air cathode current collectors can have porous structures, such as mesh forms, because current collectors with porous structures have excellent oxygen supply efficiency to the air cathode.

[0151] In the lithium-air battery of the present invention, the non-aqueous ion-conducting (electrolyte) medium disposed between the negative and positive electrodes can be a non-aqueous electrolyte containing one or more organic solvents and typically containing salts. Non-limiting examples of usable salts include known supporting electrolytes such as LiPF6, LiClO4, LiAsF6, LiBF4, Li(CF3SO2)2N, LiFSI (i.e., Li(FSO2)2N), Li(CF3SO3), and LiN(C2F5SO2)2. These salts can be used separately or in combination. The salt concentration can be in the range of 0.1 to 5.0 M. The lithium salt concentration in the electrolyte can be greater than 1.0 M, greater than 1.5 M, and greater than 2.0 M. The salt concentration can be less than 4.0 M, less than 3.2 M, and less than 2.0 M. Furthermore, a binder can be used with the ionic liquid-based electrolyte.

[0152] Example

[0153] 1.1 Materials

[0154] a. Adhesive synthesis

[0155] All chemical precursors, comprising poly(diallyldimethylammonium chloride) (PDADMA-Cl, high molecular weight (400,000-500,000) and low molecular weight (<100,000), 20 wt% in water, Aldrich), are used in receiving condition with the selected salt. The salts comprise sodium bis(fluorosulfonyl)imide (NaFSI, 99.7%, Solvionic), lithium bis(trifluoro-methylsulfonyl)imide (LiTFSI, 99%, IoLiTec), lithium bis(perfluoroethylsulfonyl)imide (LiBETI, 99%, IoLiTec), and nano-potassium fluoro-1-butanesulfonate (KC4F9SO3, 95.0%, TCI).

[0156] b. NMC base electrode

[0157] The material used for NMC-based electrodes is used in the receiving state and comprises: 1-methyl-2-pyrrolidone (NMP, suitable for HPLC, ≥99%, Sigma-Aldrich), 5 wt% poly(vinylidene fluoride) in NMP solvent (5 wt% PVDF in NMP, PVDF Mw > 10 × 10⁻⁶). 5 g / mol (KUREHA KF POLYMER), carbon black (acetylene, Alfa Aesar), and NMC 523 (Custom Cells).

[0158] c. Air electrode

[0159] Gas diffusion sheets (GDL, Quintech, GER) were vacuum-dried at 120°C for 24 hours. Ketjen Black 600 carbon (Akzonobel) was vacuum-dried at 100°C for 24 hours. Reference binder: LITHion. TM Dispersion (Ion Power Inc.) with added activation Molecular sieves are used after the initial drying process, allowing 5 days for drying. For the binder, the water content, measured by Coulumetric Karl Fischer, decreased from 252.05 ppm to 218 ppm. Anhydrous 2-propanol (anhydrous IPA, MilliPore Sigma, <0.005% H2O, ≥99.9%) and anhydrous acetonitrile (anhydrous ACN, Aldrich, <0.001% H2O, ≥99.8%) are used in the receiving state.

[0160] d. Lithium-ion battery cells

[0161] All materials were pre-dried under vacuum at 100°C for 24 hours before being introduced into an argon-filled glove box. These materials included graphite electrode foil (active material content ≥95%, Custom Cells Itzehoe GmbH) and NMC 523 cathode foil (active material content 90%, density 2.36 g / cm³). - 3, Custom Cells Itzehoe GmbH), and fiberglass sheets ( GF 6 grade, Schleicher&Schüll).

[0162] The liquid electrolyte 1M lithium hexafluorophosphate was used in ethylene carbonate: methyl ethyl carbonate (1:1 volume ratio) (LiPF6 in EC: EMC, 99.9%, Solvionic) and stored in a glove box under an argon atmosphere.

[0163] e.Li-O2 battery cells

[0164] Lithium metal (Φ8mm, 120μm thick, from Rockwood Lithium (US)) is used in receiving condition. Glass fiber sheet (Φ11.28mm, (GF / A grade) Vacuum dried at 150°C for 24 hours before use.

[0165] For electrolytes, by adding active ingredients... Molecular sieves (Aldrich, 4-8 mesh) were used to dry acrylate crosslinking agent (Aldrich) and tetraethylene glycol dimethyl ether (TEGDME, Aldrich, ≥99%), allowing 5 days for drying (water content <4.6 ppm, Karl Fisher). Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, TCI, >98.0%) was vacuum dried at 100°C for 24 hours.

[0166] 1.2 Carrying different counter anions (FSI) - TFSI - BETI - and CFSO - Synthesis of PDADMA-X

[0167] As previously reported (non-patent references 1 and 2), four polymeric ionic liquids (designated PDADMA-FSI, PDADMA-TFSI, PDADMA-BETI, and PDADMA-C4F9SO3) are synthesized via metathesis reactions. As shown in Scheme 1 below, in Cl from a commercially available aqueous solution of PDADMA-Cl polymer... -Anion exchange reactions occur between anions and commercially available monovalent salts containing positive ions Z+ (e.g., Z+ = Na+, Li+, K+) and their anions (e.g., Y- = FSI-, TFSI-, BETI-, and C4F9SO3-). Figure 1 In this context, PDADMA-FSI corresponds to Example 1, PDADMA-TFSI corresponds to Example 2, PDADMA-BETI corresponds to Example 3, and PDADMA-C4F9SO3 corresponds to Example 4. Figures 5 to 10 In Example 1, PDADMA-FSI was used; in Example 2, PDADMA-TFSI was used; in Example 3, PDADMA-BETI was used; and in Example 4, PDADMA-C4F9SO3 was used.

[0168]

[0169] Except for PDADMA-C4F9SO3, this method is the same for all polymeric ionic liquids. First, 29.68 mmol of the selected salt (Z) is added. + Y - The solution was dissolved in 10 ml of distilled water at room temperature (for Z). + -C4F9SO3, 125 ml distilled water at 60 °C, and at RT (for - The C4F9SO3 reaction (heated to 50°C) was added dropwise to an aqueous solution of 24.74 mmol PDADMA-Cl monomer units dissolved in 100 mL of distilled water. The resulting polymer immediately precipitated as a white solid powder. The mixture was stirred for 1 hour. Then, after vacuum filtration, the resulting polymer powder was washed in 300 mL of distilled water (stirred at RT for 2 hours) to remove any excess unreacted salts, and then filtered again under vacuum. Finally, the polymer powder was vacuum dried at 50°C for at least 48 hours.

[0170] Table 1: Yield (%) and mass (g) of the obtained polymer

[0171] PDADMA-FSI 8.1420 96.9 PDADMA-TFSI 9.9200 95.3 PDADMA-BETI 12.3938 95.8 <![CDATA[PDADMA-C4F9SO3]]> 10.0012 93.5

[0172] 1.3 Fabrication of Electrodes and Battery Components

[0173] 1.3.1 Lithium-ion cells

[0174] NMC cathode manufacturing

[0175] All electrode pastes were composed of NMC523, acetylene black, and binder in an NMP solvent at a weight ratio of 90:5:5. The mixture was prepared by using a planetary mixer (twice, 5 minutes each at 2000 rpm) and a rotor-stator mixer (twice, 20 m·s each). -1 The compound was prepared by mixing for 120 seconds. It was then coated with a coating machine to a thickness of 200 μm and a coating thickness of 12.5 mm. -1 The slurry was coated onto the aluminum foil at a high speed. The coated foil was then dried in a vacuum oven at 90°C for 12 hours.

[0176] Graphite || NMC Assembly

[0177] The new NMC cathode was cut using a 14mm diameter bag cutter and pressed with a hydraulic press at 6 tons to obtain approximately 2.4g.cm. - The density was 3, exhibiting the same properties as the commercially available cathode used as a reference. Finally, the prepared electrodes were vacuum-dried at 90°C for 24 hours and then introduced into a glove box.

[0178] In a glove box filled with Ar with H2O < 0.01 ppm and O2 < 0.01 ppm concentrations, the cathode was assembled into a CR2032 type button cell. Glass fiber (16 mm in diameter) was used as a separator, graphite electrode (15 mm in diameter) was used as the anode, and 120 μL of liquid electrolyte 1M lithium hexafluorophosphate in ethylene carbonate: methyl ethyl carbonate (1:1 volume ratio) was added (LiPF6 in EC:EMC, 99.9%, Solvionic).

[0179] 1.3.2 Li-O2 cells

[0180] Air electrode manufacturing

[0181] The positive electrode is formed by coating a gas diffusion layer (GDL) with a slurry containing 80 wt% carbon and 20 wt% of a selected binder. The GDL sheet is punched into a circular sample (Φ11.28 mm) and dried.

[0182] To prepare the slurry, 0.6 wt% carbon, 1.6 wt% of the selected binder, and 97.8 wt% of the selected solvent were mixed together. Anhydrous 2-propanol was used as the solvent for the reference cathode, and acetonitrile was used for the new cathode. The components were placed in a glass vial and mixed uniformly at speed 2 for at least 1 hour using Ultraturrax IKA T18. The slurry was used immediately, and 70 μL of ink was deposited on each circular GDL. These were then coated and allowed to dry at RT for 24 hours. The coated GDLs had the following average carbon loading: 0.72 mg·cm⁻¹ for the reference cathode. -2 For TFSI-based adhesives, the concentration is 0.74 mg / cm³.-2 For FSI-based adhesives, the concentration is 0.36 mg / cm³. -2 For BETI-based adhesives, the concentration is 0.80 mg / cm³. -2 ; and for CFSO-based adhesive cathodes, 0.89 mg·cm -2 .

[0183] All electrode preparation was carried out under argon atmosphere in a glove box with H2O < 0.01 ppm and O2 < 0.01 ppm concentrations.

[0184] Assembly of Li-O2 cells

[0185] A Li-O2 Swagelok cell was used and placed in a specially designed PEEK container. The electrolyte was sandwiched between the negative and positive electrodes. In the case of a liquid Li-O2 cell, two glass fiber sheets (Φ11.28 mm) impregnated with a liquid electrolyte mixture (200 μL) were used. The positive electrode was positioned with the coated side facing the electrolyte surface and an aluminum mesh was used as the current collector. Lithium metal (Φ11.28 mm) was used for the negative electrode. The stack was then secured in the PEEK Swagelok cell and transferred to a sealed PEAK container. The container was then purged of argon and replaced with oxygen.

[0186] All battery cells were assembled under argon atmosphere in a glove box with H2O < 0.01 ppm and O2 < 0.01 ppm concentrations.

[0187] 1.4 Electrochemical Characterization

[0188] 1.4.1 Lithium-ion batteries

[0189] Constant current discharge-charge

[0190] Lithium-ion cells were tested using a Multi Potentiostat MPG2-6 and VMP3-1 (Bio-Logic) via constant current discharge-charge (GDC) cycles. The voltage range was (3.1–4.2) V and the temperature was set to 25°C in the constant current chamber. All cells were conditioned at 25°C for 3 hours at OCV prior to the GDC tests. Then, based on the theoretical capacity and C-rate calculations using the mass of NMC active material, the cells were activated for two cycles at 0.3C. The experimental capacity was determined from the second GDC and calculated in grams of electrodes. Each test was repeated at least three times, and the results shown are the average with standard deviation. Figure 5 ).

[0191] Resistance measurement

[0192] The resistance is evaluated after the current pulse, also known as the IV measurement, and is described in detail in Non-Patent Reference 4. The IV measurement is performed at 25°C with different discharge current pulses (ΔI) applied at 56% state of charge (SoC56), these pulses being 0.3C, 1C, 3C, and 5C, lasting for 10 seconds, and the resulting voltage drop (ΔV) is measured. Between discharge current pulses, the cell is charged back to SoC56 at 0.3C. ΔV is defined by linearizing the voltage curve 5 seconds after startup, and the resistance is calculated using Ohm's Law. Figure 6 The results and average values ​​for at least three cells are shown.

[0193] Long loop test

[0194] Perform long-cycle testing, including 1000 constant current discharge-charge cycles at 3C at 25°C or 500 cycles at 3C at 50°C. Figure 7A and Figure 7B As shown.

[0195] 1.4.2 Li-O2 cells

[0196] Constant current discharge-charge (Li-O2 cell)

[0197] like Figure 8A and Figure 8B As shown, the Li-O2 Swagelok battery cell was cycled at a cutoff potential of 2V (discharge) and 4.6V (charge) to determine the performance within ±0.1mA·cm. -2 And their absolute discharge / charge capacity at 25°C. Testing began after 3 hours of conditioning at OCV.

[0198] Limited capacity constant current discharge-charge

[0199] like Figure 9A and Figure 9B As shown, the Li-O2 Swagelok battery cell operates at ±0.1 mA·cm⁻¹. -2 Below is a limited capacity (0.8mAh·cm) -2 The circuit was cycled through 2V (discharge) and 4.6V (charge) cutoff potentials. After conditioning at OCV and 25°C for 3 hours, the test was started.

[0200] Ratio Test

[0201] The Li-O2 Swagelok battery cell was discharged using a dynamic method, in which an increasing negative current was applied to the sample. Figure 10 Apply each current density for 15 minutes, then immediately increase it and apply it again for another 15 minutes. Continue this method of increasing the current until the cell potential drops below 2V.

[0202] 2. Results

[0203] 2.1 Lithium-ion batteries

[0204] exist Figure 5 , 6 In 7A and 7B, when used as a binder in NMC-based cathodes for lithium-ion cells, the four PDADMA-Y polymers were compared with PVDF (reference).

[0205] 2.2Li-O2 battery

[0206] exist Figure 8A , 8B Among 9A, 9B, and 10, four PDADMA-Y polymers were compared with lithium-ion Nafion binders (AE-Ref) when used as binders in air electrodes (AE) for Li-O2 cells. Here, the lithium-conducting lithium-ion Nafion structure has the following types of structures:

[0207]

Claims

1. A positive electrode active material composition for lithium-ion batteries, characterized in that, Include: (A) A mixed oxide of lithium, nickel, manganese and cobalt; (B) A fluorinated anionic salt of a polycationic polymer containing repeating units represented by formula (1) as a binder: Wherein, in the above equation (1), N + For the nitrogen atom that constitutes the quaternary ammonium cation, R 1 and R 2 Each of these is independently a substituent containing a carbon atom bonded to the nitrogen atom. The fluorinated anionic salt of the polycationic polymer contains an imide anion having one of the following structures or a perfluoroalkyl sulfonate of formula (4) as the fluorinated counterion of the polycationic polymer: F-(CF2) n -(SO3) - (4) Where n is 4.

2. The composition according to claim 1, characterized in that, In the formula (1), R 1 and R 2 Each is an alkyl group.

3. The composition according to claim 1 or 2, characterized in that, In the formula (1), R 1 and R 2 All of them are methyl groups.

4. The composition according to claim 1 or 2, characterized in that, In the formula (1), R 1 The R group is a methyl group and in the formula (1) 2 It is a butyl group.

5. The composition according to claim 1 or 2, characterized in that, The mixed oxide of lithium, nickel, manganese and cobalt has the general formula (5): LiNi x Mr y Co z O 2±α (5) Where x+y+z=1.0 and α is at most 0.

05.

6. The composition according to claim 5, characterized in that, x=0.5, y=0.3 and z=0.

2.

7. The composition according to claim 5, characterized in that, x=0.33, y=0.33 and z=0.33, or x=0.6, y=0.2 and z=0.2, or x=0.8, y=0.1 and z=0.

1.

8. A lithium-ion battery, characterized in that, Include: - A cathode comprising a positive electrode active material, wherein the positive electrode active material comprises the composition according to any one of claims 1 to 7; - Including the anode, which is a negative electrode active material; and - An electrolyte disposed between the anode and the cathode.

9. The lithium-ion battery according to claim 8, wherein, The electrolyte contains lithium salts selected from the following: LiClO4, LiTFSI and LiPF6.

10. A lithium-air battery, characterized in that, Include: - An anode containing a negative electrode active material; - The cathode uses oxygen as the positive electrode active material; and - An electrolyte disposed between the anode and the cathode. The cathode comprises a fluorinated anionic salt of a polycationic polymer containing repeating units represented by the following formula (1) as a binder: Wherein, in the above equation (1), N + For the nitrogen atom that constitutes the quaternary ammonium cation, R 1 and R 2 Each of these is independently a substituent containing a carbon atom bonded to the nitrogen atom. The fluorinated anionic salt of the polycationic polymer contains an imide anion having one of the following structures or a perfluoroalkyl sulfonate of formula (4) as the fluorinated counterion of the polycationic polymer: F-(CF2) n -(SO3) - (4) Where n is 4, The amount of the fluorinated anionic salt of the polycationic polymer is 2 wt% to 4 wt% relative to the total weight of the positive electrode material.

11. The lithium-air battery according to claim 10, characterized in that, The cathode contains carbon.

12. The lithium-air battery according to claim 11, characterized in that, The carbon is selected from one or more of the following types: carbon black, graphite, activated carbon, carbon nanofibers, carbon foam, molecular carbon, tubular carbon, and N-doped carbon.

13. The lithium-air battery according to claim 11 or 12, characterized in that, The carbon exhibits one, two, or three of the following characteristics: -in 20 and 2000m 2 Specific surface area between / g; and / or - Aperture diameter of 5 nm or larger; and / or - Average primary particle diameter from 8 to 350 nm.

14. The lithium-air battery according to claim 10, characterized in that, The liquid portion of the electrolyte contains one or more aprotic organic solvents selected from the following: cyclic carbonates, chain carbonates, cyclic esters, cyclic ethers, chain ethers, and nitriles.

15. The lithium-air battery according to claim 10, characterized in that, The electrolyte contains lithium salts selected from the following: LiClO4, LiTFSI and LiPF6.

Citation Information

Patent Citations

  • Protected active metal electrode and battery cell structures with non-aqueous interlayer architecture

    US7282295B2

  • Active metal fuel cells

    US7491458B2

  • Multifunctional cross-linked binders for lithium-sulfur battery cathodes

    WO2020237364A1

  • Manufacturing method of battery member for secondary battery

    CN108735972A

  • Composite electrode for lithium air battery, method of preparing the electrode, and lithium air battery including the electrode

    US20150155566A1